Host-mediated RNAi of a Notch-like receptor gene in Meloidogyne incognita induces nematode resistance. Issue 14 (25th April 2018) - Kohli, Deshika; Chidambaranathan, Parameswaran; Prasanth Tej Kumar, J.; Singh, Ashish Kumar; Kumar, Anil; Sirohi, Anil; Subramaniam, K.; Srinivasan, Ramamurthy; Bharadvaja, Navneeta; Jain, Pradeep K.
Abstract: GLP-1 (abnormal germline proliferation) is a Notch-like receptor protein that plays an essential role in pharyngeal development. In this study, an orthologue of Caenorhabditis elegans glp-1 was identified in Meloidogyne incognita . A computational analysis revealed that the orthologue contained almost all the domains present in the C. elegans gene: specifically, the LIN-12/Notch repeat, the ankyrin repeat, a transmembrane domain and different ligand-binding motifs were present in orthologue, but the epidermal growth factor-like motif was not observed. An expression analysis showed differential expression of glp-1 throughout the life cycle of M. incognita, with relatively higher expression in the egg stage. To evaluate the silencing efficacy of Mi-glp-1, transgenic Arabidopsis plants carrying double-stranded RNA constructs of glp-1 were generated, and infection of these plants with M. incognita resulted in a 47–50% reduction in the numbers of galls, females and egg masses. Females obtained from the transgenic RNAi lines exhibited 40–60% reductions in the transcript levels of the targeted glp-1 gene compared with females isolated from the control plants. Second-generation juveniles (J2s), which were descendants of the infected females from the transgenic lines, showed aberrant phenotypes. These J2s exhibited a significant decrease in the overall distance from the stylet to the metacorpus region, and this effect was accompanied by disruption around the metacorporeal bulb of the pharynx. The present study suggests a role for this gene in organ (pharynx) development during embryogenesis in M. incognita and its potential use as a target in the management of nematode infestations in plants.